Prioritizing transportation equity: Fare-free bus programs in Lawrence and Worcester, Massachusetts - Leib, Ginger. (Tufts University. Tisch Library., 2021)
Thesis (M.A.)--Tufts University, 2021.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Shomon Shamsuddin.; Committee: Rebecca Shakespeare.; Keywords: Urban planning, Transportation, and Public policy.